PENGARUH MEDIA PENDINGIN TERHADAP KEKERASAN MAKRO DAN MIKRO Ni – HARD IV - Elfendri - (Universitas Pasir Pengaraian, 2009)
Ni – Hard IV is white cast iron alloy with high persentage on nikel ( Ni ) and Chromium ( Cr ) . It’s material is used in machine component that need high hardness and wear resistance, like roller on cement factory that used to raw material of cement ( clay, silica, stone and coal ).On operation the component which built with Ni – Hard IV will be fricted by abrasive material of cement. The expensive price component will be wear and unfunction. We need long time to make reservation for a new one.This problem can solved by making remanufacturing compnent . The damage component can be remanucfatured by arc welding method that use air in our enviroment on atmospheric temperatur as a cooler. It’s mean we applicate the normalizing Process method